Dominik Tatarka’s Socratic intellectual and cynical plebeian ethos of resistance - Gluchman, Vasil (Studies in East European thought, 2025)
The first part of the article explores the forms of intellectual resistance that Dominik Tatarka displayed against Stalinist communist power in Czechoslovakia during the 1950s and 1960s, as reflected in his literary and essayistic works. In the second part, the author examines Tatarka’s life and work during the 1970s and 1980s, shedding light on the background of his resistance to the communist regime of “real socialism”. This resistance is illustrated through his identification with the Carpathian bandit and shepherd. The author argues that this identification represents Tatarka’s genuine stance, highlighting the hypocrisy of the communist party, which portrayed itself as a defender of workers’ interests while simultaneously persecuting the working peasants and shepherds who resisted its control.